Subsequent ovarian yolk sac tumor after operation of ovarian mature teratoma: a case report and review of the literature - Li, Shuqing; Peng, Juan; Zhang, Yajun; Liu, Dongxia; Li, Lei; Nai, Manman (Frontiers in Oncology, 2024)
Ovarian mature teratoma represents a benign ovarian tumor, while ovarian yolk sac tumor (YST, endodermal sinus tumor), is a rare malignant tumor predominantly affecting young women, often associated with a grim prognosis post-metastasis. Both ovarian mature teratoma and ovarian YST are germ cell tumors. There are few studies on the correlation between ovarian YST and mature teratoma. Recurrence or malignant transformation may occur following the surgical intervention for ovarian mature teratoma. H owever, the occurrence of YST subsequent to such procedures is notably rare. In this investigation, we reported a case involving a 24-year-old unmarried female with both mature ovarian teratoma and YST within a brief one-year interval.Regular reexamination protocols facilitated the early-stage detection of YST.The patient underwent surgical treatment, chemotherapy, and measures to preserve ovarian function, resulting in a favorable prognosis. Our primary purpose is to distill clinical insights from the diagnostic and therapeutic journey of this patient. Our purpose is to enhance medical professionals' awareness that YST may be secondary to mature teratoma . Additionally, we underscore the critical importance of routine postoperative surveillance for ovarian mature teratoma, emphasizing its pivotal role in early malignant tumor detection-a factor paramount to the prognosis of patients.